Small deletion in the critical region of Cri-du-chat syndrome associated with cat-like cry - Freitas, Catarina; Rendeiro, Paula; Costa, Maria José (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
Cri-du-chat syndrome is a rare disorder caused by a deletion of part of the short arm of chromosome 5. It is characterized by the presence of clinical features at birth, namely cat-like cry, low weight, microcephaly, and facial dysmorphism. The corresponding phenotypes vary from minimal features to a complete phenotype. Herein is described the case of an infant who presented from birth with cat-like cry and a peculiar face with a wide nasal bridge and thin upper lip. The genetic study revealed a very small deletion on the short arm of chromosome 5, which has not been described in the literature and may represent a novel variant of this recurrent deletion. Furthermore, since the main feature of this case is the cat-like cry, the considered deletion (detected only by microarray analysis) could be associated with this specific feature.